PENGARUH PENGEMBANGAN KARIER DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Rikawati Ginting Munthe; Vina Maria Ompusunggu (JURNAL REGIONOMIC, 2019)
Human resources have an important role in a company. A company will have difficulty to achieve its goals without the support of its employees. Therefore, employees who have owned the company need to be maintained and developed its quality. Career development is career enhancements owned by employees to be developed to be more potential than ever. The work environment is something that exists around the workers and that affects itself in carrying out the tasks it imposes. and job satisfaction is a positive attitude and a pleasant feeling towards the job, leadership, co-workers, work environment and other matters concerning the condition of his work. The population used in this research is all employees of PDAM Tirta Malem in Kabanjahe as many as 114 employees who then use Slovin formula in taking sample to yield 54 respondents in this research. The data used in this study is the primary data obtained directly from the results of the distribution of questionnaires from respondents in the field. Together these two independent variables namely career development variables (X1) and work environment variables (X2) affect job satisfaction variable (Y) with the value (Fcount 106.471> Ftable 3.179) thus the two independent variables have a positive and significant influence on the variable bound. Both independent variables are able to explain the dependent variable of 80.3% in the test results coefficient of determination (R2).